Good bait - Harvey, John, 1938- (Pegasus Books, 2012)
When a 17-year-old Moldovan boy is found dead on Hampstead Heath, the case falls to DCI Karen Shields and her overstretched Homicide & Serious Crime Unit. Karen knows she needs a result. What she doesn't know is that her new case is tied inextricably to a much larger web of gang warfare and organized crime which infiltrates almost every aspect of London society. Several hundred miles away in Cornwall, Detective Inspector Trevor Cordon is stirred from his day-to-day duties by another tragic London fatality. Traveling to the capital and determined to establish the cause of death and trace the deceased's daughter, Cordon becomes entangled in a complicated situation of his own. A situation much closer to Karen's case than either of them will ever know.